Sistema de costos en las PYMES del sector industrial textil - Segovia Vera, María Gabriela (2022)
The manufacturing industry is considered important in Ecuador since it is part of the nonoil Income that contributes to GDP approximately 20% only considering the city of Guayaquil. The textile and clothing industry, which belongs to the manufacturing sector, is currently affected in Ecuador by the increase in smuggling and unfair competition. Another problem that these manufacturing industries also face are the costs or high costs of their production due to lack of control and efficient recording of their incurred costs.........